The Role of Biomarkers for the Prediction of Response to Checkpoint Immunotherapy and the Rationale for the Use of Checkpoint Immunotherapy in Cervical Cancer. Issue 12 (December 2019) - Otter, S.J.; Chatterjee, J.; Stewart, A.J.; Michael, A.
Abstract: Checkpoint immunotherapy has revolutionised the way that melanoma is treated and has also shown significant effectiveness in lung, bladder, renal, and head and neck cancers. At the present time, trials of checkpoint immunotherapy in cervical cancer are at early phases, but there is very good rationale for pursuing this as a treatment option, especially as cervical cancer is a virally driven cancer and therefore should be recognised by the immune system as being foreign. This review explores the biomarkers for the selection of patients for immunotherapy in other cancers, such as programmed death ligand 1 (PD-L1) expression, tumour infiltrating lymphocytes and total mutational burden, and relates these biomarkers to cervical cancer. A PubMed search was carried out for publications published in English with the terms 'immunotherapy' OR 'cervical cancer' OR 'checkpoint blockade' OR 'tumour infiltrating lymphocytes' OR 'total mutational burden'. Articles that met these criteria and were available on PubMed before 8 October 2018 were included. The results showed that PD-L1 is positive in up to 90% of cervical cancers and that the total mutational burden is moderately high, with 5–6 mutations per megabase. In addition, the tumour microenvironment in cervical cancer has an impact on prognosis, with higher ratios of CD8+ tumour infiltrating lymphocytes to CD4+ T regulatory cells being associated with improved survival. Clinical studies to date have shown the response rate of cervical cancer to checkpoint immunotherapy to be in the region to 10–25%. Cervical cancer exhibits many of the features that have been shown to be correlated with response to checkpoint immunotherapy in other tumour sites. However, response rates to date are in the region of 10–25%. Therefore, combinations of immunotherapeutic agents or checkpoint inhibitors with radiotherapy may be required to maximise the therapeutic benefit of harnessing the host immune system to fight cancer. Highlights: Patient selection for immunotherapy is critical – PD-L1, TILs and TMB are associated with response. Cervical cancer exhibits has high PD-L1 expression, high TILs and moderate TMB. The rationale for using checkpoint immunotherapy in cervical cancer is strong. Response rates to date are 10–25% but with combination therapy this could be improved.